Array-Based Genomic Comparative Hybridization Analysis of Field Strains of Mycoplasma hyopneumoniae - Madsen, Melissa L. (American Society for Microbiology (ASM), 2007)
Mycoplasma hyopneumoniae is the causative agent of porcine enzootic pneumonia and a major factor in the porcine respiratory disease complex. A clear understanding of the mechanisms of pathogenesis does not exist, although it is clear that M. hyopneumoniae adheres to porcine ciliated epithelium by action of a protein called P97. Previous studies have shown variation in the gene encoding the P97 cilium adhesin in different strains of M. hyopneumoniae, but the extent of genetic variation among field strains across the genome is not known. Since M. hyopneumoniae is a worldwide problem, it is reasonable to expect that a wide range of genetic variability may exist given all of the different breeds and housing conditions. This variation may impact the overall virulence of a single strain. Using microarray technology, this study examined the potential variation of 14 field strains compared to strain 232, on which the array was based. Genomic DNA was obtained, amplified with TempliPhi, and labeled indirectly with Alexa dyes. After genomic hybridization, the arrays were scanned and data were analyzed using a linear statistical model. The results indicated that genetic variation could be detected in all 14 field strains but across different loci, suggesting that variation occurs throughout the genome. Fifty-nine percent of the variable loci were hypothetical genes. Twenty-two percent of the lipoprotein genes showed variation in at least one field strain. A permutation test identified a location in the M. hyopneumoniae genome where there is spatial clustering of variability between the field strains and strain 232.